A comparative study on outcome of Type I Tympanoplasty using sliced 1-mm Conchal cartilage and full-thickness Conchal cartilage for grafting - Vijay Ramalingam; Kandasamy Kamindan; Ram Karthik Murugan; Velumani Rajeswari (The Egyptian Journal of Otolaryngology, 2020)
Abstract Background This study aims at comparing the pure tone audiogram and tympanogram results of a measured thickness (1 mm) conchal cartilage graft material (1.0-mm CC) with full-thickness conchal cartilage (FTCC) used for inactive chronic suppurative otitis media (CSOM) mucosal disease with moderate size perforation. Results A total of 40 successful cartilage tympanoplasty procedures were included in the prospective quasi-randomised study. Patients aged between 15 and 55 years with inactive CSOM—moderate size perforation in the tympanic membrane were included. The patients were assessed at the end of 12 weeks with a pure tone audiogram and a tympanogram. The results were compared to know the compliance of the tympanic membrane (TM) between the two groups and the difference in audiometric gain (air-bone gap closure). The air-bone gap gain was better in the 1.0-mm CC group of patients (12) compared to the FTCC group of patients (7). The difference was statistically significant (p = 0.04). The 1.0-mm CC group of patients showed better compliance (0.43) compared to FTCC group of patients (0.73). The air volume and compliance were significantly better in the 1-mm CC group compared to the FTCC group (p = 0.031 and 0.01 respectively). Conclusion The use of sliced cartilage seems to have a better role in reconstructing the TM when compared to full-thickness cartilage as graft material. It is indeed beneficial to have a compliant TM. Though the results cannot be compared with temporalis fascia grafts, the use of 1.0-mm CC has its advantage in producing an audio logically acceptable outcome in tympanoplasty surgery.